Implementation of Zakat Accounting at the Al-Hikmah Mosque Zakat Management Agency in Soka Boyolali - Rois, Dimas Ilham Nur; Kurniati, Sari; Astungkara, Agni; Masitoh, Endang; Marwati, Fithri Setya; Hamidah, Raisa Aribatul (Journal of Universal Community Empowerment Provision, 2024)
This activity aims to raise awareness of the importance of zakat accounting and the ability to manage zakat systematically in accordance with Islamic law within the community. The activity is carried out through three stages: first, a lecture on the fundamentals of zakat accounting; second, training on zakat accounting in accordance with PSAK 109; and third, providing assistance in implementing zakat accounting during the collection and distribution of zakat. Following these activities, the zakat managers of Al-Hikmah Mosque in Soka, Boyolali Regency, have shown commitment and interest in applying zakat accounting to produce financial reports as a form of accountability to the muzaki.